A Blend of Cultures in Myanmar - Ko Gyi, Jenny (Journal of International Buddhist Studies, 2015)
A brief description on a blend as a result of coexistence of people from different countries and of different faiths. Facts are based mainly on the integration of people in Myanmar, its natives and those from neighboring countries. A short description on cultural and religious outcome is presented, followed by some salient aspects of explanation from a Buddhist point of view.